Hubungan Pengetahuan Diet Dan Perilaku Membaca Informasi Nilai Gizi Produk Makanan Kemasan Terhadap Kepatuhan Diet Pasien Penyakit Jantung Koroner (Pjk) Dengan Hipertensi Rawat Jalan Di Rsud Dr. Moewardi - Wardhani, Dipicha Triesnaputri Kusuma (2016)
Introduction: Understanding of diet and reading behavior the nutrition fact on food labels have an important role to people with coronary heart disease (CHD) and hypertension which require control of nutrient intake, especially fat and sodium. Purpose: The research aimed to analyze the correlation knowledge of diet and reading behavior the nutrition fact on food labels with diet adherence in outpatients with corononary heart disease (CHD) and hypertension. Research method: A cross sectional study was conducted in a consecutive sampling of 37 patients aged ≥ 26 years in Dr. Moewardi Hospital. Knowledge of diet and reading behavior were obtained through an interviews using questionnaires. Adherence diet was measured through an interview using a semi-quantitatif FFQ during the last 1 month. Analysis of the relationship was tested using Fisher's Exact Test. Results: Thirty (81,1%) respondents had good knowledge of diet, 22 (59,5%) respondents had a low to average reading the nutrition fact on food labels, and 20 (54,1%) respondents were categorized in non-adherence to diet. There was no significant correlation between knowledge of diet and adherence diet (p=0,680), as well as the nutrition fact on food labels and adherence diet with (p=0,157). Conclusion: Knowledge of diet and reading behavior the nutrition fact on food labels not always adequately impact to diet adherence in people with diagnose CHD and hypertention.